Importance of monitoring and availability of hydrological data for integrated water resources management - Figueiredo Pereira, Marco Alésio; Lippo Barbieiro, Bruno; Muller de Quevedo, Daniela (Sociedade & Natureza, 2020)
The environment conservation with sustainable development implantation practices to integrated natural resource management is essential for the maintenance of the environment and society. Thus, this article aims to evaluate the hydrometric monitoring of Sinos River basin, in Rio Grande do Sul state, and argue the availability importance of hydrological data for integrated water resources management – IWRM, based on hydrological data disponibility at the National Water Resources Information System – SNIRH, under the responsibility of the National Water Agency - ANA. For this, the study presents the conditions of the hydrometric monitoring Sinos River watershed and discussing the importance of making hydrological data available to IWRM. Based on information made available in the SNIRH, a survey was carried out on the historical series of rainfall, flow and water quality in stations installed in the respective basin, being evaluated whether from the hydrometric monitoring carried out, it is possible to implement IWRM. It was possible to identify that from the existing data the IWRM implementation and maintenance are compromised. Several entities monitor water resources in the basin, however, when made available, the data observed by such entities are stored on specific sites of each institution or are not even made available, which makes it difficult to acquire data for end-users. Besides, there is a need to expand the monitoring network and implement an automatic and telemetric monitoring network in the basin.